2002
DOI: 10.1002/14651858.cd001357
|View full text |Cite
|
Sign up to set email alerts
|

Amisulpride for schizophrenia

Abstract: BackgroundThe treatment of schizophrenia with old, 'typical' antipsychotic drugs such as haloperidol can be problematic, because many people treated with these drugs will su er from movement disorders. Amisulpride is said to be an "atypical" antipsychotic which induces less movement disorder and which is e ective for the negative symptoms of schizophrenia. ObjectivesTo evaluate the e ects of amisulpride as compared with placebo, typical and atypical antipsychotic drugs for schizophrenia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(5 citation statements)
references
References 61 publications
0
4
0
1
Order By: Relevance
“…A few systematic reviews also indicated that the controlled trials of second-generation antipsychotics have mainly tested only a few kinds, including risperidone, olanzapine, quetiapine, loxapine, sertindole, aripiprazole, and amisulpride, and mostly compared them with placebo controls 4350. The reviews concluded that second-generation antipsychotics had similar effects to FGAs in terms of reduction of positive symptoms.…”
Section: Pharmacological Treatmentmentioning
confidence: 99%
“…A few systematic reviews also indicated that the controlled trials of second-generation antipsychotics have mainly tested only a few kinds, including risperidone, olanzapine, quetiapine, loxapine, sertindole, aripiprazole, and amisulpride, and mostly compared them with placebo controls 4350. The reviews concluded that second-generation antipsychotics had similar effects to FGAs in terms of reduction of positive symptoms.…”
Section: Pharmacological Treatmentmentioning
confidence: 99%
“…10 At lower doses (50-300 mg/day), amisulpride enhances dopamine transmission by selectively antagonizing presynaptic autoreceptors, contributing to the drug's efficacy in addressing primarily negative symptoms, whereas at higher doses (400-800 mg/day), amisulpride antagonizes postsynaptic D2 and D3 receptors in the limbic system, which is predictive of potent antipsychotic activity. [10][11][12] Furthermore, amisulpride acts as a potent antagonist at the serotonin 5HT7 receptor, which is postulated to contribute to its antidepressant efficacy. 13,14 The limbic selectivity of amisulpride is associated with a low propensity for causing extrapyramidal side effects.…”
Section: Introductionmentioning
confidence: 99%
“…Our systematic search of the Cochrane Database of Systematic Reviews yielded a total of 37 Cochrane systematic reviews (28 for SGAs), 15 50 which generated 316 informative randomised controlled trials (243 for SGAs). Most of these studies did not include children or adolescents; 0% to 5% of studies included patients below 18 years of age, of which fewer than 10% were below the age of 18 years.…”
Section: Resultsmentioning
confidence: 99%